1993
DOI: 10.1016/s0248-4900(05)80188-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of structural analogs of putrescine on proliferation, morphology and karyotype of glioblastoma cells in culture

Abstract: In a previous study, we identified regions on the surface of tumor cells which act as acceptor sites for putrescine (Put) and studied the competition between structural analogs of Put (N,N'-tetramethyl-alpha,omega-diaminoalkanes) and Put bound to latex microspheres. A chain of four to seven carbons was necessary for inhibition of Put-latex binding to the cell surface of human glioblastoma (U251) cells. We show here that under the experimental conditions, N,N'-tetramethyl-1,4-butanediamine and N,N'-tetramethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Swelling of Golgi apparatus was previously observed using transmission electron microscopy in lymphocytes treated with DFMO or ethylglyoxal bis(guanylhydrazone) [Sakamaki et al, 1989] and was accompanied by a reduced activity of galactosyltransferase, a Golgi marker enzyme. By transmission electron microscopy, swelling of endoplasmic reticulum, transport vesicles, Golgi apparatus, or secretory vesicles was also observed in glioblastoma cells treated with putrescine analogues (N,Ntetramethyl-a,v-diaminoalkanes) [Quemener et al, 1993]. We used a ceramide and a lectin with binding sites on the medial and trans cisternae of the Golgi apparatus and observed that Golgi apparatus was enlarged and partly shifted towards the periphery of the cell.…”
Section: Golgi Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Swelling of Golgi apparatus was previously observed using transmission electron microscopy in lymphocytes treated with DFMO or ethylglyoxal bis(guanylhydrazone) [Sakamaki et al, 1989] and was accompanied by a reduced activity of galactosyltransferase, a Golgi marker enzyme. By transmission electron microscopy, swelling of endoplasmic reticulum, transport vesicles, Golgi apparatus, or secretory vesicles was also observed in glioblastoma cells treated with putrescine analogues (N,Ntetramethyl-a,v-diaminoalkanes) [Quemener et al, 1993]. We used a ceramide and a lectin with binding sites on the medial and trans cisternae of the Golgi apparatus and observed that Golgi apparatus was enlarged and partly shifted towards the periphery of the cell.…”
Section: Golgi Apparatusmentioning
confidence: 99%
“…Disturbances in the organization of cytoskeleton, notably the microfilament system, may lead to malignant cell transformation [Rao and Cohen, 1991]. There is evidence that polyamine deprivation is accompanied by structural alterations in the cytoskeleton [Balasundaram et al, 1991;Pohjanpelto et al, 1981;Pomidor et al, 1995] and Golgi apparatus [Allen, 1988;Quemener et al, 1993;Sakamaki et al, 1989]. On the other hand, remodeling of the cytoskeleton can affect the activity of ornithine decarboxylase [Pomidor et al, 1995].…”
mentioning
confidence: 99%